Pedoman Hidup Dalam Islam Yang Abadi dan Universal - Adisty Puji Nurjayanti; Meiyuri Yinriani; Tri Yolanda; Febriani Febriani; Hanifah Hafsah; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Books of Allah, which include the Torah, Gospel, Psalms, and the Quran, are divine revelations given as a guide for humanity. In the context of Islam, recognizing and understanding these texts is essential, as they provide moral and ethical guidance relevant to everyday life. The Quran, as the final book, reaffirms previous teachings and invites believers to reflect upon and apply divine messages in a modern context. The teachings within these texts are universal, offering values of goodness, justice, and compassion that remain relevant throughout time. Furthermore, these books serve as sources of inspiration and solutions to various life challenges, helping to shape the character and morality of individuals and society. By adhering to the teachings of the Books of Allah, Muslims can cultivate spirituality, strengthen their relationship with Allah, and create a harmonious and just society.